The Differences of Kinematic Parameters Javelin throw between Male and Female Finalists World Championship (Berlin, 2009-Daegu, 2011) - Ratko Pavlovic; Kemal Idrizovic; Vladan Savic; Mensur Vrcic; Nikola Radulovic; Simeonov, Aleksandar (American Journal of Sports Science and Medicine, 2020, Vol. 8, No. 1, 8-15, 2020)
Kinematic parameters are an indispensable segment in the analysis of all throwing disciplines, including javelin throw. They are also an indicator of possible differences between competitors of different or the same rank of the competition and are an important factor for achieving a good result. The aim of the study was to determine the spatial and temporal differences of kinematic parameters in the javelin throw between the male and female finalists of the World Championships. Methods: The study was conducted on a sample of finalists in the World Athletics Championships (Berlin 2009-Daegu 2011) with the aim of determining the differences between the kinematic parameters of the male and between the female javelin throwers. The sample included a total of 32 competitors in both categories. To obtain the necessary results, a t-test for independent samples was applied. Result: statistically significant differences were confirmed between male finalists in 60% of kinematic parameters: release velocity (t=3,504; p<0,004), angle of yew (t=4,664; p<0,000), length of delivery stride (t=2,444, p<0,028), distance to foul line (t=5,120), duration of impulse stride (t=-4,462, p<0,001), duration to release (t=-4,837, p<0,000). In women, significant differences in 40% of parameters were confirmed: angle of release (t=-,365, p<0,005), angle of yew (t=9,182; p<0,000), duration of impulse stride (t=-4,140, p<0,001), duration to release (t=-4,409, p<0,001). Conclusion: Generally speaking, this research showed that significant differences were observed between male finalists and between female finalists. Mostly, these are kinematic parameters that have proven to be paramount in the resultant performance of these championship throwers. One should not forget the influence of exogenous factors, above all air currents and javelin behavior as an aerodynamic device. An ideal biomechanical model of the thrower can be made based on the differences in the kinematic parameters of the top medal winners at the Berlin WCh in 2009 and the Daegu WCh in 2011.
Keywords: elite athletes; kinematic parameters; javelin throw; differences